Current status of family-based outcome and process research - Diamond, GS; Serrano, AC; Dickey, M; Sonis, WA (Journal of the American Academy of Child and Adolescent Psychiatry, 1996)
Objective: To review family-based treatment research. A growing body of research and several meta-analytic reviews demonstrate that family-based treatments are effective for a variety of child and adolescent disorders. In addition, an emerging tradition of family-based process research has begun to identify important ingredients of effective family psychotherapy. This article reviews these advances and their implications for future research. Method: Selected studies on the treatment of schizophrenia, depression, anxiety, eating disorders, attention deficit, conduct disorder, and substance abuse are reviewed, as well as several process research and meta-analytic studies. Results: Family-based therapies have been shown to be effective for treating schizophrenia, conduct disorder, and substance abuse. Some data support their effectiveness in the treatment of eating disorders. Few studies have targeted internalizing disorders. A process research tradition is emerging, but it is in need of methodological advances, Meta-analytic studies suggest that family-based therapies are as effective as other models. Conclusions: More well-designed studies with diverse populations are needed to assess accurately the effectiveness of this increasingly popular treatment approach.
57 citations (Crossref) [2023-10-31] tex.researcherid-numbers: diamond, Guy/X-8695-2019 tex.unique-id: ISI:A1996TL43200007
Keywords: anxiety; attention deficit disorder; child parent relation; depression; dept.mft; family therapy; feeding disorder; medical research; mental disease; outcome research; priority journal; process research; psychotherapy; review; risk factor; schizophrenia; substance abuse